Mechanisms modulating foam cell formation in the arterial intima: exploring new therapeutic opportunities in atherosclerosis - La Chica Lhoëst, M. T.; Martinez, A.; Claudi, L.; Garcia, E.; Benitez-Amaro, A.; Polishchuk, A.; Piñero, J.; Vilades, D.; Guerra, J. M.; Sanz, F.; Rotllan, N.; Escolà-Gil, J. C.; et al. (Frontiers in Cardiovascular Medicine, 2024)
In recent years, the role of macrophages as the primary cell type contributing to foam cell formation and atheroma plaque development has been widely acknowledged. However, it has been long recognized that diffuse intimal thickening (DIM), which precedes the formation of early fatty streaks in humans, primarily consists of lipid-loaded smooth muscle cells (SMCs) and their secreted proteoglycans. Recent studies have further supported the notion that SMCs constitute the majority of foam cells in advanced atherosclerotic plaques. Given that SMCs are a major component of the vascular wall, they serve as a significant source of microvesicles and exosomes, which have the potential to regulate the physiology of other vascular cells. Notably, more than half of the foam cells present in atherosclerotic lesions are of SMC origin. In this review, we describe several mechanisms underlying the formation of intimal foam-like cells in atherosclerotic plaques. Based on these mechanisms, we discuss novel therapeutic approaches that have been developed to regulate the generation of intimal foam-like cells. These innovative strategies hold promise for improving the management of atherosclerosis in the near future.